Fertility, Pregnancy, and Parenthood Discrimination in the Labour Market: A Systematic Review - Morien El Haj; Stijn Baert; Luc Van Ootegem; Elsy Verhofstadt; Louis Lippens (Institute of Labor Economics (IZA), 2024)
Disparities in labour market outcomes between parents and non-parents arise partly from discriminatory practices. Understanding these unfair practices is essential for fostering workplace equity. Our systematic review of the literature summarises employer discrimination based on various manifestations of parenthood in multiple labour market outcomes. Unlike previous studies, our review encompasses not only motherhood but also fatherhood and the stages preceding parenthood, namely fertility and pregnancy. In terms of labour market outcomes, we consider discrimination in hiring, remuneration, promotion, and dismissal. We also focus exclusively on experimental research, enabling causal conclusions about discrimination and its underlying mechanisms. Our synthesis suggests that employers consistently penalise women in the labour market when they have children, during pregnancy, and during their fertile years. In contrast, men often experience no adverse effects or even a premium when they have children. Researchers frequently find evidence of statistical discrimination as the primary explanation for their findings. Employers appear to rely predominantly on information based on norms and stereotypes to make decisions about parents in the labour market. We offer a roadmap for academics, policymakers, and employers to map and mitigate this phenomenon in the long term. In particular, we highlight fruitful directions for future research, including (i) more broadly assessing the effects of fertility, (ii) more effectively manipulating parenthood in experiments, (iii) more frequently investigating dismissal as a labour market outcome, and (iv) more profoundly examining the mechanisms of parenthood discrimination.
Keywords: J13; J16; J71; 330; parenthood; pregnancy; fertility; discrimination; labour market outcomes; systematic review